Reflectance confocal microscopy follow-up of multifocal superficial basal cell carcinomas treated with imiquimod 5% cream - Yun-Min Zou; Xiaohong Zhu; Rushan Xia (Mattioli1885, 2022)
Background： Patients with multifocal superficial basal cell carcinomas (sBCC) require a non-invasive treatment and follow-up with a non-invasive technique. Imiquimod 5% cream is a new non-invasive therapy for BCC. Reflectance confocal microscopy (RCM) is a non-invasive, real-time imaging technique. Methods：The efficacy of imiquimod 5% cream for the treatment of multifocal sBCC was evaluated, as well as the potential of RCM for assessing therapeutic effects. We reported four patients with 34 sBCC lesions were treated with imiquimod 5% cream. RCM was performed in the baseline and at 12 weeks, 24 weeks and 52 weeks after starting treatment. Results： Of 34 lesions treated with imiquimod 5%, 32 responded to the treatment and showed complete clinical clearing. Two subclinical BCC lesions were identified by RCM. The complete tumor clearance rate was 88.2%, and the efficiency rate was 97.1%. No lesion recurred at 24-month follow-up. RCM identified previously described confocal features of BCC and was more sensitive than clinical examination. Local skin reactions were relieved after expectant treatment. Conclusions： Imiquimod 5% cream may be useful for the treatment of multifocal sBCC, and its side effects are easy to manage. RCM can be used for non-invasive monitoring of treatment response and improved the tumor clearance rate.